A new species of shieldtail snake (Reptilia: Squamata: Uropeltidae) from Kolli Hill complex, southern Eastern Ghats, peninsular India - S.R. Ganesh; N.S. Achyuthan (Journal of Threatened Taxa, 2020)
We describe a new species of shieldtail (uropeltid) snake, Uropeltis rajendrani sp. nov., from the Kolli Hill complex of the southern Eastern Ghats in Tamil Nadu, India.  The new species belongs to the U. ceylanica group and is differentiated from related species in having 16–17:16–17:15–16 dorsal scale rows; 145–158 ventral scales; 8–11 pairs of subcaudals; dorsum uniform brown, anteriorly powdered with yellow mottling; venter brown, scales outlined with yellow.  This endemic species with a restricted range is known only from atop Kolli Hill complex, inhabiting higher elevation (> 900m) evergreen forests, where it is the only known member of this genus.